The actin-binding protein α-adducin is required for maintaining axon diameter - Leite, SC (2016)
The actin-binding protein adducin was recently identified as a component of the neuronal subcortical cytoskeleton. Here, we analyzed mice lacking adducin to uncover the function of this protein in actin rings. a-adducin knockout mice presented progressive axon enlargement in the spinal cord and optic and sciatic nerves, followed by axon degeneration and loss. Using stimulated emission depletion super-resolution microscopy, we show that a periodic subcortical actin cytoskeleton is assembled in every neuron type inspected including retinal ganglion cells and dorsal root ganglia neurons. In neurons devoid of adducin, the actin ring diameter increased, although the inter-ring periodicity was maintained. In vitro, the actin ring diameter adjusted as axons grew, suggesting the lattice is dynamic. Our data support a model in which adducin activity is not essential for actin ring assembly and periodicity but is necessary to control the diameter of both actin rings and axons and actin filament growth within rings.